Abdominal Mondor’s disease presenting as acute abdominal pain. - Cervellin, Gianfranco; Creta, Michele; Riva, Michele; Di Comite, Vincenzo; Buttarelli, Lorenzo; Lippi, Giuseppe (Acta Biomedica Atenei Parmensis, 2013)
We describe here the case of 41 yrs old male patient, who was admitted to the emergency department complaining for abdominal pain lasting for two days. The patient self-reported a history of idiopathic deep vein thrombosis five yrs before the visit. A subcutaneous cordlike induration, tender and painful, was clearly palpable in the left lower abdominal quadrant. Routine blood tests did not reveal any substantial abnormality, except increased D-dimer concentration. Ultrasound evaluation of the abdominal wall revealed diffuse thrombosis of the left superficial inferior epigastric vein, involving several small tributaries branches, extended until 1.5 cm from the confluence with the common femoral vein, which was finally classified as an atypical case of Abdominal Mondor’s disease. Complete thrombophilia screening was negative. The patient was discharged with warfarin therapy 48 hours from admission. At 30 days follow-up, the patient self-reported a nearly complete recovery.